Optimising PCM thermal storage systems for maximum energy storage effectiveness - Nasrul Amri, Mohd Amin; Belusko, Martin; Bruno, Frank; Liu, Ming (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/